Optimasi Proses Ekstrusi Texturized Vegetable Protein di PT XYZ - Dede Yoga Ahmadi; Budi Nurtama; Tjahja Muhandri (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2022)
Texturized vegetable protein (TVP) is one of the meat analogue products made by modifying the structure of vegetable protein come to be meat-like texture. Several advantages could be obtained by consuming meat analogue. It could reduce the risk of disease and could be consumed by someone who could not consume meat, either because of health problems or beliefs meat consumption will increase continually inline with increasing population, economic level, and public awareness to nutrition. The TVP using was increased as a protein source alternative. The TVP demand of PT. XYZ increase continued to, but the number of production machines was limited. The companies need to optimize their available machines to meet their demand. This research aimed to optimize the production capacity of TVP. Defatted soy flour was used as the source of protein. Several parameter used in this research were flour flow capacity, water flow capacity, screw rotation speed, and extruder temperature. The response parameters used were water absorption, water content, color, bulk density, and grain shape. The data was collected by 21 runs that is repeated twice for each run. The optimization process was carried out using Design Expert 10 (DX-10) through Response Surface Method (RSM). The optimum of process conditions combination of the TVP extrusion were: flour flow capacity 225kg/hour; water flow capacity 35.54 Hz; extruder temperature 130.70°C; and the screw rotation speed 375.18 rpm. The verification result showed that the value of each response was within the Confident Interval (CI) range.